Macroscopic Anatomy of the Stifle Joint in the Pampa's Deer (Ozotoceros bezoarticus-Linnaeus, 1758) - Horst Erich König; Sokol Duro; William Pérez (MDPI AG, 2023)
The objective of this paper was to describe the anatomy of the stifle joint (Articulatio genus) of the pampas deer (Ozotoceros bezoarticus, Linnaeus, 1758) by dissection and imaging studies. Twenty-six pelvic limbs were used for gross dissection, and four stifle regions from two animals were used for radiography and magnetic resonance imaging (MRI). The stifle joint of the pampas deer comprised the femoropatellar joint (joint between the distal part of the femur and the patella), and the femorotibial joint joined the femoral condyles to the proximal extremity of the tibia. The general anatomy of the stifle joint, including the overall morphology of the joint with its bones, complementary parts, means of attachment, and anatomical relationships, was like that of other ruminant species of similar size. Imaging techniques such as MRI allow adequate visualization of most components of the stifle joint.